7 - Towards a New Map of Africa through Rastafari ‘Works’ - Niaah, Jahlani A. H. (Africa Development, 2021)
This paper seeks to broaden the notion of the African Public sphere to include the historical Diaspora by highlighting the works of Mortimo Planno, cultural historian – Rastafari luminary and plenipotentiary – in closing the void between Africa and its Diaspora, through examining Planno’s definition of the African public sphere, as articulated in his general writings and main text: ‘The Earth Most Strangest Man’, as well as travelogues articulating his discourse on Back-to-Africa. Mortimo Planno is credited as having tutored reggae icon Bob Marley and many others in the faith of Rastafari which was to emerge as a new world religion and way of life out of Jamaica. Planno, an outstanding pan- African scholar and activist, travelled to the United States of America, Canada, the United Kingdom and some fifteen African states, lecturing on the Movement developed in Jamaica, celebrating the Emperor of Ethiopia, Haile Selassie I as God incarnate. For more than fifty years, this elder was seen as the de facto leader of the Rastafari movement of Kingston. The study applies Paulo Freire’s theory of a ‘pedagogy of liberation’ to assess whether Rastafari thinkers such as Planno can be seen as facilitating a trans-Atlantic conscientisation towards remedial African national development and liberation from what Garvey (1927) described as ‘mental slavery’.